Tingkat Pengetahuan Keluarga tentang Perawatan Orang dengan Gangguan Jiwa di UPTD Kesehatan Kecamatan Sukorejo Kota Blitar - Rifqi Himmatul Aliyah (STIKes Patria Husada Blitar, 2016)
The family is an important factor in determining the success of the nursing care of patients with mental disorders. One of the mental patients relapse due to ignorance of the family about the care of people with mental disorders. The purpose of this study was to determine the level of knowledge about family care of people with mental disorders. The method in this research was descriptive. The research instruments used a questionnaire. The population in this study was families who care for patients with mental disorders in health UPTD District Sukorejo blitar city. The sample was 33 families taken by quota sampling. The result showed that 45.45% (15 families) had less knowledge 36,37% (12 families) had sufficient knowledge, and 18.18% (6 families) had a good knowledge. This lack of knowledge on the details of the knowledge in accordance with the treatment of people with mental disorders were physically ie 60.61% (20 families) lack of knowledge, psychological treatment that were 60.61% (20 families) lack of knowledge, in social care that were 81.82% (27 families) lack of knowledge, spiritual care that were 78.79% (26 families) lack of knowledge of family and good knowledge about the treatment of people with mental disorders showed 60.61% (20 families) visits of maintenance treatment regimen. This research was expected to be a reference to improve the understanding of the family aboutthe care of people with mental disorders.